The influence of somatic, auditory, visual, and intellectually (SAVI) learning models on science learning outcomes - Baiq Annisa Yuliana; Mohammad Liwa Ilhamdi; Heri Hadi Saputra (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
This study aims to determine the effect of the SAVI learning model on the science learning outcomes of various styles of materials on the fourth-grade elementary students at SDN 1 Sandik, Lombok, Indonesia. The type of research used is quasi-experiment design type nonequivalent control group design. The sampling technique used is purposive sampling. The total number of samples is 60 students. The data analysis in this study used SPSS version 21.0 for windows. The statistical test in this study used the t-test and the normalized gain test. Based on the results, the average value of the experimental class changed, namely from the pre-test value of 56.40 and the post-test value of 71.57. The results of statistical calculation data analysis using the t-test (paired-sample t-test) obtained 6.931 > 2.045. A normalized gain test is done to find out how significant the effect is. The results of the normalized gain test that the researcher got were 0.3 by the normalized gain score category included in the medium category. This study shows an effect of the SAVI learning model on the science learning outcomes of fourth-grade students at SDN 1 Sandik.